Rancang Bangun Aplikasi Penjadwalan Kuliah Di Institut Bisnis Dan Informatika Stikom Surabaya Dengan Menggunakan Algoritma Genetika - Denny Septyanto; Tutut Wurijanto; A. B. Tjandrarini (Jurnal Sistem Informasi Universitas Dinamika, 2018)
One academic activities carried out by the Institute of Business and Information Stikom Surabaya is a lectures scheduling activities. Facts that occurred in the preparation of the current class schedule and the process requires considerable time. This occurs because the need to classify and sort the data written using paper media and draw up a schedule with the help of Microsoft Excel. The difficulties encountered when preparing the class schedule is the schedule should be adjusted to the terms and policies that have been determined by matching them one by one. Based on these problems, made a lecture scheduling application using Genetic Algorithms. Lecture scheduling application with regard to the data compiled estimates of the number of participants of each course, the data subject to be held, the data capacity of each course, data on the number of lecturers, the data competence of lecturers, lecturers teaching load data, and data classrooms. The results showed that the application of this lectures scheduling has can produce in one semester class schedules in accordance with the existing terms and policies. Results of testing for lectures scheduling as many as 75 classes obtained the best parameter to the value of chromosome 30, the amount of generation of 30, the probability of crossover and mutation probabilities 70 30. By using the best parameters of the test results produced by the class schedule with an average success rate of 86% to 30 trials.